Synthesizing and reconfiguring metastable modular metamaterials for adaptive wave propagation control. (3rd March 2020) - Liu, Xiang; Cai, Guoping; Wang, K.W.
Abstract: This research uncovers new insights and novel methodology to synthesize tunable wave propagation characteristics in a metastable modular metamaterial by reconfiguring the modules and system metastable states. The reconfigurable criteria of the one-dimensional (1D) metastable modular metamaterial are rigorously investigated to provide insights on the tunability of such metamaterials. A sufficient condition for reconfigurability is derived analytically, following the numerical solutions of the sufficient and necessary condition. An inverse problem is then formulated to achieve desirable band structures via switching the modular internal configurations and metastable states in one-dimensional and two-dimensional (2D) metamaterials. Exploiting the correlation between the unique on-off feature of the modules' metastable states and the binary nature of the Genetic Algorithm (GA) approach, GA is utilized to decide the reconfiguring action of each module to achieve the desired band structure. With this method, we show that wave propagation in 1D and 2D metastable modular metamaterials can be controlled adaptively by on-demand reconfiguration of the modules.